A REVIEW OF DIGITAL TRANSFORMATION OF EDUCATION IN OMAN (Journal of Business Management and Accounting, 2021)
This article reviewed the digital transformation of education in Oman. There are many problems facing regular education in Oman. In this study, the issue of digital transformation in Omani education is mainly discussed. The aim of this study is to review the impact of the environment, human and financial resources, and educational knowledge on the speed of digital transformation of education, as the speed of digital transformation leads to the development of digital transformation performance in the Sultanate of Oman. The results indicated that the environment, human resources, finance and knowledge have a significant impact on the performance of digital transformation. The inclusion of digital transformation revealed the conceptual model for the effect of complementary mediation on the relationship between digital knowledge and digital transformation as well as the performance of technology as a whole. This study 42 Journal of Business Management and Accounting, Vol. 11, Number 2 (July) 2021, pp: 41–59 demonstrates the importance of digital transformation along with e-learning and meeting user expectations. The Secondary Research Approach method was used by reviewing many articles from various sources such as websites, books, journals, and scholarly research, from July to November 2020.The results contributes significantly to both theory and practice by promoting the use of digital transformation.